Mamíferos da região do baixo Rio Tocantins - Valente, Roseth de Nazaré Pantoja (Museu Paraense Emílio Goeldi, 2023)
The eastern portion of Pará State can be considered as one of the best studied Amazonian areas, with inventories and research dating back to the 18th century. However, knowledge about the local diversity remains with unresolved issues, especially regarding the distribution limits of some species. Due to the accelerated environmental degradation it has suffered, with high rates of deforestation, this region can be seen as a priority area for conservation in the Brazilian Amazon. The area bathed by the lower third of the Tocantins River harbors one of the highest concentrations of taxa in the Eastern Amazon. However, the importance of the role played by this river in the biogeography of mammals in the region is controversial. This study aims to update knowledge on mammal diversity in the Amazonian stretch of the Tocantins River, seeking to help clarify questions related to the zoogeography of the region, and providing empirical bases for the application of conservation strategies in this area. The data were collected based on records from the collections of the Museu Paraense Emílio Goeldi, Museu Nacional, and Museu de Zoologia da Universidade de São Paulo, in addition to a review of the available literature. The results indicated the presence of 128 species, distributed in 33 families and 11 orders in the study area. The distribution map of localities indicated many points where there are records of mammals in the study area. However, most of these points represent isolated collections, which do not reveal the real diversity of each sampling area. According to current knowledge, two genera of primates (Mico and Callicebus) have their distributions apparently restricted to the left bank of the Tocantins River. Although the literature indicates the same pattern for Ateles, the presence of this genus in the Tocantins-Xingu interfluve is still unclear. Another 3 mammalian genera showed differentiated terminal taxa between the banks of this river